2020
DOI: 10.1021/acs.molpharmaceut.9b01294
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Total Clearance Prediction: Computational Machine Learning Model versus Bottom-Up Approach Using In Vitro Assay

Abstract: The in vitro–in vivo extrapolation (IVIVE) approach for predicting total plasma clearance (CLtot) has been widely used to rank order compounds early in discovery. More recently, a computational machine learning approach utilizing physicochemical descriptors and fingerprints calculated from chemical structure information has emerged, enabling virtual predictions even earlier in discovery. Previously, this approach focused more on in vitro intrinsic clearance (CLint) prediction. Herein, we directly compare these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 68 publications
0
42
0
Order By: Relevance
“…Kosugi and Hosea 24 constructed a prediction model using in-house compounds as a regression model for rat CL. Their models used 330 molecular descriptors and eight algorithms including random forest and radial basis functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kosugi and Hosea 24 constructed a prediction model using in-house compounds as a regression model for rat CL. Their models used 330 molecular descriptors and eight algorithms including random forest and radial basis functions.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In addition to using the features of compounds, Kim et al 33 and Wang et al 37 used biological descriptors related to membrane transporters and constructed a prediction model which improved the prediction performance. Kosugi and Hosea 24 improved the prediction performance of their model using in vitro experimental values as a new feature in addition to molecular descriptors. These findings indicated that the inclusion of different types of features might improve the prediction performance of QSAR models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each prediction model was generated with StarDrop (StarDrop v6.5.0, Optibrium Ltd, Cambridge, UK) according to the previously described method ( 23 , 24 ). StarDrop uses 2D SMARTS-based descriptors, which are counts of atom types and functionalities, along with whole molecule properties such as molecular weight (M.W.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a rearrangement of the well stirred model [55,56], classification bands can be used to categorize compounds into low, medium or high clearance, assuming an extraction ratio of 0.3 and 0.7 for the low and high boundaries, respectively. Next, this can be scaled to intrinsic clearance (µL/min/mg protein) using the relevant liver weights [57] and microsomal protein concentration [50,58,59] obtained from the literature and computational data. For humans, an CL int < 8.6 µL/min/mg protein defines a low intrinsic clearance classification band, whereas an CL int > 47.0 µL/min/mg protein defines a high intrinsic clearance classification band.…”
Section: Ent-a013 Exhibits Slow Depletion In Human Liver Microsomesmentioning
confidence: 99%